Job Stress and Work Environment as Antecedents of Cyberloafing Behavior: Implications for Employee Performance - Astri Ayu Purwati; Yuriana Liem; Muhammd Luthfi Hamzah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of job stress and work environment on cyberloafing behavior and their implications for employee performance at PT. Perry Eka Bina Mandiri, Pekanbaru, Indonesia. The study employed a quantitative descriptive approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) for data analysis. The population consisted of all 34 employees of the company, and a census (saturated sampling) technique was applied, resulting in 34 respondents. The findings indicate that job stress does not have a significant effect on cyberloafing behavior or employee performance. The work environment has a significant negative effect on cyberloafing behavior but does not significantly influence employee performance. Furthermore, cyberloafing behavior has a significant negative effect on employee performance. These results highlight that cyberloafing plays a more direct role in influencing performance outcomes compared to job stress and work environment within the proposed model.